Methods to Investigate the Deformability of RBC During Malaria - Depond, Mallorie; Henry, Benoit; Buffet, Pierre; Ndour, Papa Alioune (Frontiers in Physiology, 2020)
Despite a 30% decline in mortality since 2000, malaria still affected 219 million subjects and caused 435,000 deaths in 2017. Red blood cells (RBC) host Plasmodium parasites that cause malaria, of which Plasmodium falciparum is the most pathogenic. The deformability of RBC is markedly modified by invasion and development of P. falciparum. Surface membrane area is potentially impacted by parasite entry and development, the cytoskeleton is modified by parasite proteins and cytosol viscosity is altered by parasite metabolism. RBC hosting mature parasites (second half of the asexual erythrocytic cycle) are abnormally stiff but the main reason for their absence from the circulation is their adherence to endothelial cells, mediated by parasite proteins exposed at the infected-RBC surface. By contrast, the circulation of non-adherent rings and gametocytes, depends predominantly on deformability. Altered deformability of rings and of uninfected-RBC altered by malaria infection is an important determinant of malaria pathogenesis. It also impacts the response to antimalarial therapy. Unlike conventional antimalarials that target mature stages, currently recommended first-line artemisinin derivatives and the emerging spiroindolones act on circulating rings. Methods to investigate the deformability of RBC are therefore critical to understand the clearance of infected- and uninfected-RBC in malaria. Herein, we review the main methods to assess the deformability of P. falciparum infected-RBC, and their contribution to the understanding of how P. falciparum infection causes disease, how the parasite is transmitted and how antimalarial drugs induce parasite clearance.